2018
DOI: 10.1016/j.jaut.2018.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune liver disease serology in acute hepatitis E virus infection

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
15
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 41 publications
5
15
2
Order By: Relevance
“…Although no patient developed autoimmune liver disease in the further course, AIH-typical autoantibodies (except for anti-SLA) were found in over 50% of patients. 42 In line with the results from our study these findings strongly support the recommendation to exclude HEV infection in patients with suspected autoimmune liver disease, especially because immunosuppressive therapies can lead to chronic infections and potentially complicated courses.…”
Section: Con Clus Ionssupporting
confidence: 90%
“…Although no patient developed autoimmune liver disease in the further course, AIH-typical autoantibodies (except for anti-SLA) were found in over 50% of patients. 42 In line with the results from our study these findings strongly support the recommendation to exclude HEV infection in patients with suspected autoimmune liver disease, especially because immunosuppressive therapies can lead to chronic infections and potentially complicated courses.…”
Section: Con Clus Ionssupporting
confidence: 90%
“…The rate of ANA positivity (>1:160) in our study population was more or less comparable to previously reported data. Terziroli Beretta-Piccoli and Wu et al reported ANA positivity rates ranging between 33% and 37% [11,12]. In contrast to our study, however, they only tested patients with acute hepatitis E, and not with chronic or asymptomatic HEV infection.…”
Section: Discussioncontrasting
confidence: 63%
“…The presence of autoantibodies has been described in HEV infections and in other viral diseases [11][12][13]. Using three cohorts of patients, we studied a possible link between the type of HEV infection and the immune phenomena, such as the presence of autoantibodies and cryoglobulins.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations